Deliverability and efficacy of R‐CHOP chemotherapy in very elderly patients with diffuse large B‐cell lymphoma: an Australian retrospective analysis. Issue 11 (November 2015) - Millar, A.; Ellis, M.; Mollee, P.; Cochrane, T.; Fletcher, J.; Caudron, A.; Webster, B.; Trotman, J.
Abstract: Background: Elderly patients with diffuse large B‐cell lymphoma (DLBCL) have an inferior prognosis, due in part to advanced age and pre‐existing comorbidities, with reduced tolerability and deliverability of standard R‐CHOP chemotherapy. Aims: To examine the deliverability, toxicity and efficacy of R‐CHOP and the prevalence of the germinal and non‐germinal phenotype DLBCL in an elderly Australian cohort. Methods: This retrospective analysis included patients ≥75 years diagnosed with DLBCL. Comprehensive chemotherapy and toxicity data were collected for patients treated with R‐CHOP. Baseline demographics and chemotherapy characteristics were compared with progression‐free (PFS) and overall survival (OS). Immunohistochemical staining identified the prevalence of the non‐germinal centre (non‐GCB) phenotype. Results: Of the 111 patients, 92 (83%) commenced R‐CHOP with 26/92 (28%) receiving ≤4 cycles. Median average relative dose (ARD) was 0.80 (0.07–1.17). Median average relative dose intensity (ARDI) was 0.89 (0.33–1.18). Serious adverse events occurred in 77% of patients with ≥Gd3 adverse events in 74%. Overall response rate was 85%. Two‐year PFS was 63% and OS 74%. ARD and performance status ≥2 were significant prognostic factors for PFS and OS but not ARDI. Non‐GCB‐phenotype was identified in 44/72 (61%) of patients with immunohistochemical data. Conclusion: Despite high response rates and respectable survival estimates, the absence of standard therapy in 17% of patients, and dose reductions and serious toxicity of R‐CHOP in this Australian cohort highlights the need for the development of less toxic yet efficacious treatments for very elderly patients with DLBCL. The high prevalence of the non‐GCB phenotype highlights the potential value of targeted biological therapy for this demographic.